2016
DOI: 10.1097/eja.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference as a predictor of difficult intubation and difficult mask ventilation in morbidly obese patients

Abstract: Univariate analyses showed that difficult intubation was associated with neck circumference, males, BMI more than 50  kg  m(-2), American Society of Anesthesiologists (ASA) status and waist circumference, and difficult mask ventilation with neck circumference, males, BMI more than 50  kg  m(-2) and thyromental distance. Multiple logistic regression analysis showed that neck circumference more than 42  cm (P = 0.044) and BMI more than 50  kg  m(-2) (P = 0.017) were independent predictors of difficult intubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
81
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 19 publications
10
81
1
4
Order By: Relevance
“…We took the value with highest TPR and FPR on the graph as our cut off [ Figure 1 ]. Our upper limit for RHTMD was 17.13 and was lower than in other Indian studies[ 13 14 16 ] but was similar to that reported by Liaskou et al . [ 19 ] Schmitt proposed an RHTMD of 25 or more for prediction of difficult laryngoscopy in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We took the value with highest TPR and FPR on the graph as our cut off [ Figure 1 ]. Our upper limit for RHTMD was 17.13 and was lower than in other Indian studies[ 13 14 16 ] but was similar to that reported by Liaskou et al . [ 19 ] Schmitt proposed an RHTMD of 25 or more for prediction of difficult laryngoscopy in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
“…There are multiple studies stating male gender as a predictor of difficult intubation. [ 16 ] Our study too had more males with difficult laryngoscopy. We had a total of 429 males with 22.8% (98) having difficult laryngoscopy compared to 1575 females with 10.09% (159) difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Neck circumference of >42 cm and BMI of >50 kg·m −2 (super obesity) are two independent predictors of difficult intubation 15. Dixit et al16 observed that 44.4% of super obese patients had C-L grade 3 and 4 views compared to 20.4% of the morbidly obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Superobese patients with BMI ≥ 50 kg/m 2 and neck circumference > 42 cm are considered to be 50 times more likely to experience difficulties in intubation [5]. In our patient, restenosis of the previously resected trachea was a factor for refusing anesthesia and any elective surgery in non-experienced centers.…”
Section: Discussionmentioning
confidence: 63%